PENGARUH KINERJA PEMDES, KESADARAN MASYARAKAT DAN PENGETAHUAN PAJAK TERHADAP KEPATUHAN PEMBAYARAN PBB KELURAHAN BANDAR KIDUL - Rahayu, Ajeng Nafa Dianty; Zaman, Badrus; Widiawati, Hestin Sri (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This research aims to determine the influence of Village Chief (PEMDES) performance, community awareness, and tax knowledge on compliance in making Property Tax (PBB) payments in Bandar Kidul Sub-district, Bandar Kidul District, Mojoroto Regency. The research method employed is quantitative causality. The data collection technique involved the use of questionnaires through GoogleForms. The data analysis techniques utilized encompass classic assumption tests, multiple linear regression analysis, and hypothesis testing. The research findings conclude that, partially, the performance of PEMDES, awareness, and tax knowledge significantly affect PBB payment compliance. Furthermore, collectively, the performance of PEMDES, awareness, and tax knowledge significantly influence PBB payment compliance. While there have been several researchers investigating taxpayer compliance factors, few have explored the impact of PEMDES performance, community awareness, and tax knowledge in Bandar Kidul Sub-district, Mojoroto District, Kediri City.